2020
DOI: 10.1097/scs.0000000000007026
|View full text |Cite
|
Sign up to set email alerts
|

Nasoalveolar Molding: Assessing the Burden of Care

Abstract: Over the last 3 years a shift at our institution has taken place in which patients who would have been offered nasoalveolar molding (NAM) as an adjunct to cleft lip repair (repair after 3 months) have instead undergone early cleft lip repair (ECLR) (2–5 weeks of life) without NAM. This study sought to examine the financial and social impact of the transition away from NAM to ECLR. The efficacy of NAM is limited by patient compliance to a rigorous treatment schedule requiring weekly visits for appliance adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…10 Instead of presurgical NAM, early cleft lip repair (ECLR) provides another option in a protocol that decreases the burden of health costs. 14 In our study, however, the NAM therapy was covered by state insurance. Travel costs of public transport were also covered by state insurance.…”
Section: Discussionmentioning
confidence: 90%
“…10 Instead of presurgical NAM, early cleft lip repair (ECLR) provides another option in a protocol that decreases the burden of health costs. 14 In our study, however, the NAM therapy was covered by state insurance. Travel costs of public transport were also covered by state insurance.…”
Section: Discussionmentioning
confidence: 90%
“…While advantages of ECLR include improved aesthetic outcomes, wound healing, and parental mental health (Burianova et al, 2017), there is persistent concern regarding the effects of anesthetic agents on neonatal neurological development. Our institution developed a novel DBNAP for patients undergoing ECLR without any increase in adverse events compared to traditional volatile anesthetic agents (Wlodarczyk et al, 2021b). Several primate and rodent models have shown neuronal apoptosis with the use of GABA agonist and NMDA receptor antagonists (Ikonomidou et al, 1999; Jevtovic-Todorovic et al, 2003; Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…NAM, however, has several disadvantages: biweekly dental clinic visits, parental adherence to an appliance protocol, and significantly higher costs to the healthcare system and families compared to ECLR (Abbott and Meara, 2012;Esmonde et al, 2018;Wlodarczyk et al, 2021b). In one study by Wlodarczyk et al (2021b), diverting the first 100 ECLR patients from NAM resulted in a decreased cost burden of $ 368 700 ($ 111 727 per year) on the healthcare system. Included in this cost burden is lost wages for families with a child receiving NAM, which totals $2738.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that these costs could be reduced with passive presurgical treatment [ 31 ]. This could also counteract early cleft lip surgery in the first weeks of life, which has been propagated to reduce the burden of health care costs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%